Strengthening Quality, Growth, and Performance in Agriculture Finance : Lessons from India - AgriFin (World Bank, Washington, DC, 2013)
This report presents the key message, lessons, and insights from agrifin's first knowledge exchange event, held in Hyderabad, India, March 7-12, 2011. Agrifin is a special initiative aimed at building capacity in agriculture finance for commercially-oriented smallholders and small and medium enterprise (SME) agribusiness market segments. The initiative, managed by the World Bank, through generous support from the bill and Melinda gates foundation, provides matching grant funding to financial institutions and regulated microfinance institutions that have a demonstrated potential for scaling up sustainable business models in agriculture finance. in complement to the grant funding, agrifin fosters learning in the agriculture finance space by facilitating peer-to-peer exchanges, such as this event, as well as by documenting and sharing lessons learned with the broader public, based but not exclusively on agrifin grant recipients' experiences. This event provided an opportunity for agrifin's partner financial institutions in Burkina Faso, Cambodia, Mali, Mozambique, Nepal, Senegal, Sri Lanka, and Uganda, together with senior World Bank experts, to learn about sustainable practices in agricultural lending. Participants had the opportunity to engage with senior officials from three prominent financial institutions in India (Andhra Bank, BASIX, and HDFC Bank).